Digital Threat: The Influence of Social Media Use on Climate Anxiety in Emerging Adulthood Moderated by Gender - Ardelia, Vania; Jaro'ah, Siti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
Several studies have investigated the mental health impacts of climate change, with only a few examining the effect of social media use on climate anxiety. The spread of information through social media can exacerbate anxiety, including climate change anxiety. Therefore, this study aimed to examine the influence of social media use on climate anxiety among emerging adults. A cross-sectional design was used, with data collected from both males (n = 55) and females (n = 225). Participants completed a self-administered questionnaire that included demographic characteristics, the Social Media Use Integration Scale, and the Climate Anxiety Scale. Data were analyzed using a moderator analysis technique. The results showed social media use significantly predicted climate anxiety among emerging adults, confirming that higher social media use could directly increase climate anxiety. However, gender had no significant moderating effect on the relationship. These results had important theoretical and practical implications for understanding climate anxiety, especially in the digital era.